Carved arabesques in malay traditional houses: skill, tradition and preservation of identity - Kamaruddin, Zumahiran; Said, Ismail (Kulliyyah of Architecture and Environmental Design, IIUM, 2015)
This study aims to explore the placement and fabrication of the wood carvings within the old Kelantan and Terengganu timber houses. The main objective of this study was to examine the placement of wood carvings in the houses with emphasis on its fabrication as house components. Non-interactive and interactive methods of data collection were employed as research tactics. The non-interactive method involved archival review of 25 sets of measured drawings of the Kelantan and Terengganu timber houses from the Centre for Study of Built Environment in the Malay World at the Universiti Teknologi Malaysia. The interactive method involved semi-structured interviews with five woodcarvers to obtain their verification on the findings from the analytical review which served as the primary data. The study found that architectural components of the houses especially perforated ventilation panels of walls, doors and windows were fabricated in different composition of carvings with intricate arabesque design. Regularity in the placement of these components give spatial identity to the principal spaces such as ‘rumah ibu’ (core house), ‘serambi’ (verandah) and main bedrooms. Fabrication of the carvings as house components was in parallel with their structural layouts and functions. This architectural inclination addresses the relationship of creativity, skill and intrinsic knowledge of the Malay craftsmen in keeping the tradition upon the exquisite forms of the houses in general and the carved arabesques in particular. The regional identity of the carvings has been practically and consistently sustained through ages, which suggests preservation of architectural identity within the traditional living environment.